Mastócitos de camundongos BALB/c e C57BL/6 e a susceptibilidade a infecção por Toxoplasma gondii (cepas RH e ME-49) - Ferreira, Gabriela Lícia Santos (2005)
In the present work it was studied: the morphological and ultrastructural characteristics of mast cells located in the peritoneal cavity of BALB/c and C57BL/6 mice and morphological and ultrastructural alterations of these mast cells after 24 and 48 hours of infection with RH strain of T. gondii; the number of the mast cells, neutrophils, macrophages and lymphocytes from peritoneal cavity of BALB/c and C57BL/6 mice after 24 and 48 hours of infection with RH strain of T. gondii, by optical microscopy; the morphological characteristics of mast cells located in the small intestine of BALB/c and C57BL/6 mice; and the morphological and quantitative features of mast cells located in the small intestine of BALB/c and C57BL/6 mice after 8 days of infection with ME-49 strain of T. gondii and/or treated with 48/80 compound; the histopathological changes of the small intestine BALB/c and C57BL/6 mice after 8 days of infection with ME-49 strain of T. gondii and tissue parasitism in this organ, liver and brain from BALB/c and C57BL/6 mice after 8 days of infection with ME-49 strain of T. gondii and/ or treated with 48/80 compound, by immunohistochemistry. The light and transmission electron microscopy analysis revealed that the mast cells from the peritoneal exsudate of BALB/c and C57BL/6 mice, presented similar characteristics like shape, cytoplasmic granules quantity and feature. Similarity, mast cells from the peritoneal exsudate of BALB/c and C57BL/6 T. gondii infected mice, presented similar characteristics between both lineages of mice. The light microscopy analysis showed an increased number of mast cells, neutrophil and macrophage in peritoneal exsudate of BALB/c mice after 24 hours of infection with RH strain of T. gondii, these influx didn t occurr in C57BL/6 lineage. The number of mast cells in the small intestine from BALB/c mice was superior than the number of mast cells observed in the small intestine from C57BL/c mice. The number of parasitized field in the small intestine was superior in C57BL/6 mice. These results reveals the role of the mast cells in the mechanisms of regulation of the inflammatory response against T. gondii and may be related with their sensitivity or resistance of the both mice lineage, BALB/c and C57BL/6. After comparison between mice lineage, BALB/c and C57BL/6, it was observed that the lymphocytes number was statistically significant after 24 and 48 hours of PBS inoculation in C57BL/6 mice s peritoneal exsudate. The light microscopy analysis from the different regions of the small intestine, duodenum, proximal jejunum, distal jejunum and ileum, of BALB/c and C57BL/6 mice showed that mast cells were found, preferentially, in the submucosa and muscle stratum. By light microscopy, mast cells from the small intestine of BALB/c and C57BL/6 mice after 8 days of infection with ME-49 strain of T. gondii, presented different characteristics in the quantity and shape of the cytoplasmic granules. The number of mast cells from the small intestine of BALB/c and C57BL/6 after 8 days of infection with ME-49 strain of T. gondii, presented superior in BALB/c mice. The mast cells were, preferentially, located in the duodenum form BALB/c and C57BL/6 mice infected or not infected. The histopathology analysis, after 8 days of infection with ME-49 strain of T. gondii, showed an inflammatory infiltrated more intense in the small intestine from C57BL/6 mice. T. gondii was found in the small intestine, liver and brain from BALB/c and C57BL/6 mice after 8 days of infection with ME-49 strain of T. gondii, and/or treated with 48/80 compound by immunohistochemistry. In the small intestine of BALB/c mice the number of mast cells doesn t change after 8 days of infection with ME-49 strain of T. gondii, and after 12 days of treatment with 48/80 compound.